2018
DOI: 10.1039/c8ce00897c
|View full text |Cite
|
Sign up to set email alerts
|

Phase evolution of KLaF4 nanocrystals and their effects on the photoluminescence of Nd3+ doped transparent oxyfluoride glass-ceramics

Abstract: Quantity of cubic (α-phase) and hexagonal (β-phase) KLaF4 nanocrystals (NCs) tailored by doping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…It should be noted that unlike the hexagonal LaF 3 oxyfluoride NCs, 33,39 cubic NaLuF 4 NCs form from each phase-separated droplet, this is typical behavior of alkali lanthanide tetrafluoride NCs. 13,40,41 The size of the NCs is thus similar to the size of the precursor phase-separated F I G U R E 1 (A) XRD patterns for undoped, xTm 3+ -doped (x = 0.1, 0.5 mol%) and 0.5Tm 3+ -yYb 3+ -codoped (y = 1, 2 mol%) GCs. (B) Magnified regions of (111) peak of the corresponding GCs regions, and then they grow more with the adequate heat treatment in temperature and time.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It should be noted that unlike the hexagonal LaF 3 oxyfluoride NCs, 33,39 cubic NaLuF 4 NCs form from each phase-separated droplet, this is typical behavior of alkali lanthanide tetrafluoride NCs. 13,40,41 The size of the NCs is thus similar to the size of the precursor phase-separated F I G U R E 1 (A) XRD patterns for undoped, xTm 3+ -doped (x = 0.1, 0.5 mol%) and 0.5Tm 3+ -yYb 3+ -codoped (y = 1, 2 mol%) GCs. (B) Magnified regions of (111) peak of the corresponding GCs regions, and then they grow more with the adequate heat treatment in temperature and time.…”
Section: Resultsmentioning
confidence: 89%
“…7,8 Moreover, the controlled crystallization mechanism allows obtaining NCs with sizes up to 50 nm in which the RE ions are incorporated, dismissing the Rayleigh scattering and maintaining the transparency. 9 Glass-ceramics based on LaF 3 , YF 3 , and RLnF 4 (R = K, Na) [10][11][12][13] phases have been described as efficient luminescent materials. In particular, sodium lanthanide tetrafluorides, with the general formula NaLnF 4 , (with Ln = Gd, Y, La, or Lu) have been reported to be ideal hosts for RE 3+ ions that can act as emitting centers and have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…For the last ten years, the GlaSS group at Ceramics and Glass Institute (CSIC) focused attention on the preparation of transparent glass-ceramics with low-phonon fluoride crystals, such as LaF 3 , NaGdF 4 , NaLuF 4 , KLaF 4 , etc., with rare-earth ions as dopants for optical applications [29,30,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. The main emphasis was on maximizing the crystalline fraction, maximum incorporation of the RE dopant, and further enhancement in luminescence profile.…”
Section: Oxyfluoridegcsmentioning
confidence: 99%
“…In the case of 0.1 mol% of the Nd 3+ -doped sample, only after heat treatment at 660 • C for times longer than 144 h, β-KLaF 4 nanocrystals were formed. In the case of 0.5 mol% of Nd 3+ -doped sample, β -KLaF 4 nanocrystals were formed only for times longer than 15 h, and the authors concluded that hexagonal nanocrystals needed longer growth times [68].…”
Section: Oxyfluoridegcsmentioning
confidence: 99%
“…[2][3][4][5][6][7] Higher photoluminescence (PL) efficiencies and better energy-transfer (ET) are usually obtained in OxGCs with respect to glasses due to the controlled crystallization of low phonon-energy uoride nano-crystals (NCs) that are good hosts for Rare-Earth (RE) ions. [8][9][10][11][12][13][14][15][16][17][18] Most glass systems are based on aluminosilicate compositions that show good mechanical, thermal and chemical properties together with improved PL features of uoride NCs doped with RE ions. Most studies were performed on bulk samples but the possibility to prepare GC bers is also becoming a hot-spot for novel optical materials.…”
Section: Introductionmentioning
confidence: 99%